Effect of occupation-based interventions in patients with haematopoietic malignancies undergoing chemotherapy: A pilot randomised controlled trial - Akira Sagari; Yuta Ikio; Nobuko Imamura; Kayoko Deguchi; Toko Sakai; Takayuki Tabira; Toshio Higashi (Hong Kong Journal of Occupational Therapy, 2018)
Background/objective Chemotherapy for cancer negatively affects activities of daily living and quality of life. This study aimed to validate and compare the efficacy of two different interventions in patients with haematopoietic malignancies undergoing chemotherapy: (1) occupation-based interventions, designed using the Aid for Decision-making in Occupation Choice (ADOC) (an iPAD application) and (2) impairment-based interventions. ADOC helps promote decision-making during activities and participation in occupation-based goal setting. The impairment-based intervention group served as the comparison group and underwent impairment-based interventions focusing on dysfunction. Methods In this single-blinded pilot randomised controlled trial, 19 participants received an occupation-based intervention (n = 9) or an impairment-based intervention (n = 10). The treatment period comprised two sessions. Recruitment, compliance and outcome completion rates were calculated for the study. Effect sizes were examined for outcomes regarding physical performance, instrumental activities of daily living and quality of life as evaluated by a blinded assessor. Results In this study, 24.8% (28/113) of the eligible patients with haematopoietic malignancies were enrolled, and 67.9% (19/28) of these were retained up to the post-assessment stage. Recruitment (25%) and compliance (68%) rates were satisfactory. The Functional Assessment of Cancer Therapy-General emotional well-being and total scores were significantly higher for the occupation-based intervention group than for the impairment-based intervention group (both p < 0.05; d = 0.54, d = 0.51, respectively). Other outcomes showed no significant differences. Conclusion Occupation-based interventions designed using the ADOC application were useful for patients with haematopoietic malignancies.